2022
DOI: 10.3389/fsurg.2022.935410
|View full text |Cite
|
Sign up to set email alerts
|

Immediate direct-to-implant breast reconstruction: A single center comparison between different procedures

Abstract: BackgroundThe increased incidence of conservative mastectomy operations (nipple- and skin- sparing) has increased the frequency of immediate breast reconstructions (IBR). In order to guarantee patients the best possible aesthetic outcome, the least chance of complications and moreover, the least postoperative pain, the technique with prepectoral prosthetic pocket was recently reconsidered with the use of ADM. This is the first study using Fortiva® in prepectoral breast reconstruction, and it compares the outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Eighteen studies reported postoperative infection rates 3,4,11–26 . Overall, the rate of surgical site infections was 2.6% (n = 35/1369) and 4.1% (n = 73/1767) after prepectoral and subpectoral implants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eighteen studies reported postoperative infection rates 3,4,11–26 . Overall, the rate of surgical site infections was 2.6% (n = 35/1369) and 4.1% (n = 73/1767) after prepectoral and subpectoral implants, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported postoperative hematoma 3,11–13,15–18,20–26 . Overall, the rate of hematoma was 2.1% (n = 25/1207) and 3.5% (n = 56/1580) after prepectoral and subpectoral implant reconstruction, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations